Spatial Classification of the Transportation Network in the Holy City of Karbala and Its Importance in Sustainable Development - Abbas Anouz, Ahmed Yahya (Journal of Tikrit University for Humanities, 2024)
Urban transport has gained special importance through the important role it plays in economic, social and cultural development leading to sustainable development, in addition to being considered one of the most important infrastructures on which development plans in every country depend, as it has contributed to the improvement of means of transport in facilitating the process of movement and transport. Reducing transportation costs, reducing the rate of traffic accidents and reducing their severity, which in turn it leads to reducing injuries and material losses resulting from these accidents. Transport also encourages the establishment of various industries that produce the materials and tools needed by vital projects such as roads, bridges, etc., as most of these materials and tools are now manufactured locally, with international specifications and high quality. This achieves a significant and clear impact in the areas of sustainable development. The research focused on the importance of explaining the types of urban transportation network in the holy city of Karbala in terms of sustainable development. The research reached the following most important results: The urban transport network in the city is characterized by the presence of six classifications of urban transport, each of which is defined according to its spatial characteristics, and the most common are the hierarchical (morphological) classification and the functional classification. The diversity of the spatial classification of the urban transport network in the city and the variation in traffic rates on it made it insufficient to accommodate the function of transportation and traffic, especially with regard to its carrying capacity for the number of vehicles, especially after the year 2003 due to the improvement in the economic level of most families, which contributed to the ease of purchasing a vehicle, especially Employees, and this doubled the problems of transportation and traffic of all kinds. Despite some problems that the urban transport network suffers from, it performs an important function in all aspects of sustainable development, and this is what will make it a good network for future generations through continuous work to improve its system and spatial trends.